BUSINESS AND TECHNOLOGY-RELATED ENGLISH BORROWINGS IN UZBEK PUBLICISM - Sapayeva Marjona (World Scientific Research Journal, 2025)
Abstract: This study explores the influence of English borrowings in Uzbek publicism, particularly in business and technology-related contexts. With globalization and digital advancements, many English terms have entered Uzbek media, often due to the lack of native equivalents or the perception of English words as more prestigious. The paper categorizes these borrowings by field, examines their adaptation into Uzbek grammar and pronunciation, and discusses the role of the Uzbek Terminology Commission in proposing native alternatives. While borrowings facilitate modernization, their increasing use raises concerns about linguistic identity and the dominance of foreign terms. The study emphasizes the importance of promoting Uzbek equivalents to maintain linguistic integrity while adapting to global influences.